ENHANCING STUDENTS’ COGNITIVE ABILITIES THROUGH THE DEVELOPMENT OF THEIR LINGUISTIC-COMMUNICATIVE COMPETENCE (Scientific journal of the Fergana State University, 2026)
This article comprehensively analyzes the issue of enhancing students’ linguistic-communicative competence to stimulate their cognitive potential. Linguistic-communicative competence encompasses skills such as effective language use, precise expression of concepts, engaging in debates, and participating in social interactions. Cognitive abilities refer to mental processes including attention, memory, reasoning, analysis, synthesis, problem-solving, and creativity. The article is structured according to the IMRAD model and thoroughly explores the topic through advanced scientific theories, methodological foundations, experimental observations, and in-depth discussions.